Analisis Tingkat Kepuasan Konsumen terhadap Beras Premium BULOG Kota Lhokseumawe Di Kecamatan Banda Sakti - Raihan Humaira Putri Rizal; Sofyan Sofyan; Safrida Safrida (Jurnal Ilmiah Mahasiswa Pertanian, 2022)
This. BULOG Premium Rice is a type of rice managed by BULOG which is of premium quality with a maximum broken grain rate of 15% and must not contain groats. This study aims to analyze the level of satisfaction of general consumers and special consumers of sembako program with BULOG premium rice in Lhokseumawe City in Banda Sakti District. Based on the type of data used in this study, primary data were obtained through direct interviews and questionnaires with general consumers and special consumers of sembako program. The data analysis method used in this study is the Customer Satisfaction Index (CSI). The results of the general consumer CSI calculation show that general consumer satisfaction with BULOG's premium rice is 92.05%, which means that general consumers are very satisfied with the quality of BULOG's premium rice and the results of the CSI calculation of consumers specifically for sembako program show that consumer satisfaction specifically for sembako program for BULOG premium rice is 95.42%, which means that consumers specifically for sembako program are also very satisfied with BULOG's premium rice.